Effectiveness and acceptability of parent training via telehealth among families around the world. Issue 4 (29th September 2019) - Tsami, Loukia; Lerman, Dorothea; Toper‐Korkmaz, Ozlem
Abstract : Teaching parents to conduct functional analyses and to implement functional communication training is an efficacious approach for treating socially maintained problem behavior (Derby et al., 1997). Research has found that delivering this assessment and intervention package via telehealth technologies is efficient and acceptable to caregivers in the United States (Wacker et al., 2013b). We replicated this work with families residing in rural and urban areas of eight countries. Two behavior therapists located in the United States conducted appointments in the participants' native languages, using interpreters as needed. Parent‐implemented functional analyses and treatment with functional communication training were highly effective in reducing problem behavior in children diagnosed with autism. Furthermore, parents rated the procedures as acceptable and indicated that the treatment would be effective with their children. These findings indicate that telehealth technologies are a viable option for clinicians to provide behavior analysis services to families around the world.